2015
DOI: 10.1111/luts.12105
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Lower Urinary Tract Symptoms in Women Aged 40 and Over

Abstract: The most common LUTS was urgency in women aged 40 years and older. Recurrent urinary tract infection was determined as the most significant risk factor for LUTS, followed by chronic illness, chronic constipation, higher BMI and parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
1
16
1
2
Order By: Relevance
“…Studies have shown that constipation is a risk factor for LUTS . Additionally, Liao et al stated that healthy lifestyle, regular exercise, and proper urinary habits would decrease the problem of not completely emptying the bladder and LUTS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that constipation is a risk factor for LUTS . Additionally, Liao et al stated that healthy lifestyle, regular exercise, and proper urinary habits would decrease the problem of not completely emptying the bladder and LUTS .…”
Section: Discussionmentioning
confidence: 99%
“…Two or more micturitions per night was defined as nocturia . A body mass index (BMI) <18.5 was considered as underweight, 18.5 to 24.9 as normal weight, and > 25 as overweight…”
Section: Methodsmentioning
confidence: 99%
“…(14,34,35) Kadın hemşirelerde AÜSS ve tuvalet alışkanlıklarının incelendiği bir çalışmada, uzun süre idrarı tutma ve yapmama gibi sağlıksız tuvalet alışkanlıklarının AÜSS'yi arttırdığı belirlenmiştir. (36) Kadınların yaş ortalamasının 40'ın üzerinde olduğu çalışmalarda, (37,38) yaş faktörünün AÜSS'yi etkilemediği belirtilse de yapılan birçok çalışma AÜSS'nin risk faktörlerinden birinin yaş olduğunu ve yaş arttıkça AÜSS'nin de arttığını göstermektedir. (19)(20)(21)23,28,(39)(40)(41) Wennberg ve ark.…”
Section: Alt üRiner Sistem Semptomlarında Risk Faktörleriunclassified
“…The overall prevalence of overactive bladder (OAB) in Europe is 16.6% in the population over 40 years old (male, 15.6%; female, 16.4%) [ 1 ]. The prevalence of OAB tends to increase with age [ 2 , 3 ]. It can interfere with quality of life and social activities [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%